Amplification of GTP-cyclohydrolase 1 gene in Plasmodium falciparum isolates with the quadruple mutant of dihydrofolate reductase and dihydropteroate synthase genes in Ghana - Osei, Musah (PLoS One, 2018)
Sulfadoxine-pyrimethamine (SP) is used as malaria chemoprophylaxis for pregnant women and children in Ghana. Plasmodium falciparum resistance to SP is linked to mutations in the dihydropteroate synthase gene (pfdhps), dihydrofolate reductase gene (pfdhfr) and amplification of GTP cyclohydrolase 1 (pfgch1) gene. The pfgch1 duplication is associated with pfdhfr L164, a crucial mutant for high level pyrimethamine resistance which is rare in Ghana. The presence of amplified pfgch1 in Ghanaian isolates could be an indicator of the evolution of the L164 mutant. This study therefore determined the pfgch1 copy number variations and SP resistance mutations in clinical isolates from Ghana. One hundred and ninety-two (192) blood samples collected from children aged ≤14 years with uncomplicated malaria in 2013–14 and 2015–16 were used. Quantitative real-time polymerase chain reaction (qRT-PCR) was used to detect the pfgch1 copy number and nested PCR-Sanger sequencing used to detect mutations in pfdhps and pfdhfr genes. Twelve parasites (6.3%) harbored double copies of the pfgch1 gene out of the 192 samples. Of the 12, 75% had the pfdhfr I51-R59-N108, 92% had the pfdhps G437 mutant, 8% had the pfdhps E540 and 67% had the SP resistance haplotype IRNG. No L164 was detected in samples with amplified pfgch1. The rare T108 mutant associated with cycloguanil resistance showed predominance (60%) over N108 in the 2015–16 isolates. The observation of parasites with increased copy number of pfgch1 gene is indicative of the future evolution of the rare quadruple pfdhfr mutant, I51-R59-N108-L164, in Ghanaian parasites. Mutant pfdhps isolates also had increased gch1 copy number suggestive that it may also facilitate sulphadoxine resistance. The selection of parasites with pfgch1 gene amplification will enhance the sustenance and persistence of parasites with SP resistance in the country. Policy makers need to begin the search for a replacement chemoprophylaxis drug for malaria vulnerable groups in Ghana.